Implementasi Persyaratan Calon Pemimpin dalam Undang-undang Nomor 6 Tahun 2014 pada pasal 33 Tentang Desa perspektif Fiqh Siyasah. - Annisa Dwi Audia Lubis; Dermina Dalimunthe (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This article discusses the implementation of the requirements for prospective leaders in article 33 of law number 6 of 2014 concerning villages in Natal District, Mandailing Natal Regency from the perspective of Fiqh Siyasah. The type of research used in this research is field research with an empirical normative legal approach. The data source for this research is the data source used is primary data, which is data obtained from the Secretary of Sikara-kara IV Village, head of RT, community of Sikara-kara IV Village. secondary data is data that includes documents, books, journals, articles and those related to research, while data collection techniques are through interviews, observation and documentation while data analysis techniques use descriptive qualitative techniques. The results of this study indicate that the Requirements for the Implementation of Candidate Leaders have not been implemented properly, in the sense that the law has not been complied with in the election of leaders in Sikara-kara IV Village, this needs to be corrected so that there are laws that must be obeyed or obeyed properly. From this research it can be concluded that the requirements to become a leader in Siyasah Fiqh studies must be fair, honest, trustworthy, intelligent, like the characteristics of the Prophet Muhammad SAW.